2016
DOI: 10.3390/w8040122
|View full text |Cite
|
Sign up to set email alerts
|

Bivariate Drought Analysis Using Streamflow Reconstruction with Tree Ring Indices in the Sacramento Basin, California, USA

Abstract: Long-term streamflow data are vital for analysis of hydrological droughts. Using an artificial neural network (ANN) model and nine tree-ring indices, this study reconstructed the annual streamflow of the Sacramento River for the period from 1560 to 1871. Using the reconstructed streamflow data, the copula method was used for bivariate drought analysis, deriving a hydrological drought return period plot for the Sacramento River basin. Results showed strong correlation among drought characteristics, and the drou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 75 publications
0
4
0
1
Order By: Relevance
“…This suggests that D. cinerea growth rings can be used as a proxy for climatic variations wherever it is present. This finding is echoed by Kwak et al (2016) who showed that soil moisture or groundwater near flowing streams influenced tree ring width growth and the size of the rings was proportional to the amount of moisture received.…”
Section: Lessons Learnt From Arid and Semi-arid Savannasmentioning
confidence: 90%
See 1 more Smart Citation
“…This suggests that D. cinerea growth rings can be used as a proxy for climatic variations wherever it is present. This finding is echoed by Kwak et al (2016) who showed that soil moisture or groundwater near flowing streams influenced tree ring width growth and the size of the rings was proportional to the amount of moisture received.…”
Section: Lessons Learnt From Arid and Semi-arid Savannasmentioning
confidence: 90%
“…3), tree ring width did not correspond to the amount of rainfall received. This fact was attributed to runoff effects, where certain species do not add significant biomass under flooded conditions (e.g., Schulman 1945;Astrade and Bégin 1997;Kwak et al 2016). Thus, there is an optimum maximum soil moisture threshold for D. cinerea.…”
Section: Lessons Learnt From Arid and Semi-arid Savannasmentioning
confidence: 99%
“…En este estudio se incluyeron cronologías de P. menziesii procedentes de dentro y fuera de la cuenca del río Piaxtla, pero esto no impidió crear una CR con una señal climática común, la cual reflejó estadísticamente la variabilidad que ha ocurrido en la cuenca o región hidrológica de estudio. Lo anterior confirma que los registros de los anillos de crecimiento preservan información de regiones geográficas más amplias que la delimitación de una sola cuenca, como lo han señalado otros autores (Brito-Castillo et al, 2003;Kwak et al, 2016;Lara, Villalba, & Urrutia, 2008;Stahle y Cleaveland, 1992 La factibilidad de la CR y la correlación con la precipitación y datos de caudal medio permitió la reconstrucción histórica de estas variables, lo que confirma la hipótesis del estudio y demuestra el uso potencial de los anillos de crecimiento en el estudio de los recursos hídricos, particularmente cuando los datos de medición instrumental son limitados o inexistentes (Mundo et al, 2012;Woodhouse, Gray y Meko, 2006). Las redes dendrocronológicas y su relación con el clima y con la hidrología se han empleado en varios estudios (Cook y Jacoby, 1983;Villanueva-Díaz et al, 2005;Woodhouse et al, 2006;Woodhouse, Stahle y Villanueva Diaz, 2012;Villanueva et al, 2017) y, dada la alta correlación observada en este trabajo, se debería considerar con más frecuencia en México; por ejemplo, para cuantificar la oferta de servicios ambientales hidrológicos o los efectos de cambio climático en las cuencas forestales.…”
Section: Discussionunclassified
“…In the study of the hydrological droughts can be mentioned, among others, the works of Shiau et al (2007), Kwak et al (2012), Michele et al (2013), Salvadori & Michele (2015), Hamdi et al (2016), Kwak et al (2016a), Kwak et al (2016b), Zhao et al (2017) and Dodangeh et al (2017). These studies focus exclusively on the bivariate analysis of the joint return period of the severities and durations of the drought events.…”
Section: Introductionmentioning
confidence: 99%